Characterization of Putative Virulence Factors of Pseudomonas aeruginosa Strain RBS Isolated from a Saltern, Tunisia: Effect of Metal Ion Cofactors on the Structure and the Activity of LasB. (23rd July 2020) - Rigane, E.; Dutoit, R.; Matthijs, S.; Brandt, N.; Flahaut, S.; Belghith, K. S.
Abstract : Pseudomonas aeruginosa is a ubiquitous Gram-negative bacterium able to survive in diverse environments such as soil, plants, freshwater, and seawater. P. aeruginosa can be an opportunistic pathogen to humans when their immune system is deficient. Its pathogenicity may be linked to the production of virulence factors. We isolated P. aeruginosa strain RBS from the saltern of Sfax in Tunisia. In this study, we characterized the halotolerance, antibiotic susceptibility, and some virulence factors of strain RBS. High NaCl concentrations inhibited growth and motility. However, biofilm formation was enhanced to protect bacteria against salt stress. Among the 18 antibiotics tested, quinolones and tetracycline showed a significant inhibitory effect on growth, motility, and biofilm formation of strain RBS. β -Lactams, however, did not have any inhibitory effect on neither bacterial growth nor motility. In some cases, resistance was due, in part, to biofilm formation. We also showed that RBS produces two proteases, LasB and AprA, which have been shown to be implicated in host infection. LasB was further characterized to study the role of metal ions in enzyme stability. It possesses two distinct metal ion-binding sites coordinating a calcium and a zinc ion. The effect of metal ion chelation was evaluated as well as substitutions of residues involved in metal ion binding. Impairing metal ion binding of LasB led to a loss of activity and a sharp decrease of stability. Our findings suggest that the binding of both metal ions is interdependent as the two metal ions' binding sites are linked via a hydrogen bond network.